Resistive-Pulse Sensing Inside Single Living Cells - Pan, Rongrong; Hu, Keke; Jia, Rui; Rotenberg, Susan A; Jiang, Dechen; Mirkin, Michael V (Journal of the American Chemical Society, 2020)
Resistive-pulse sensing is a technique widely used to detect single nanoscopic entities such as nanoparticles and large molecules that can block the ion current flow through a nanopore or a nanopipette. Although the species of interest, e.g., antibodies, DNA, and biological vesicles, are typically produced by living cells, so far, they have only been detected in the bulk solution since no localized resistive-pulse sensing in biological systems has yet been reported. In this report, we used a nanopipette as a scanning ion conductance microscopy (SICM) tip to carry out resistive-pulse experiments both inside immobilized living cells and near their surfaces. The characteristic changes in the ion current that occur when the pipet punctures the cell membrane are used to monitor its insertion into the cell cytoplasm. Following the penetration, cellular vesicles (phagosomes, lysosomes, and/or phagolysosomes) were detected inside a RAW 264.7 macrophage. Much smaller pipettes were used to selectively detect 10 nm Au nanoparticles in the macrophage cytoplasm. The in situ resistive-pulse detection of extracellular vesicles released by metastatic human breast cells (MDA-MB-231) is also demonstrated. Electrochemical resistive-pulse experiments were carried out by inserting a conductive carbon nanopipette into a macrophage cell to sample single vesicles and measure reactive oxygen and nitrogen species (ROS/RNS) contained inside them.